Shape and deformation measurements of rough surfaces by phase-shifting digital holography - Yamaguchi, Ichirou (Photonics Letters of Poland, 2021)
In digital holography recording as reconstruction of holograms are performed digitally by modern photonic devices to increase of optical non-contacting measurements of various kinds of surfaces including both specular and rough surfaces. In this article we discusses these features of digital holography using phase shifting techniques that has much extended its capabilities. Full Text: PDF References G. Bruning, D.R. Herriott, J.E. Gallagher, D.P. Rosenfeld, A.D. White, D.J. Brangaccio, "Digital Wavefront Measuring Interferometer for Testing Optical Surfaces and Lenses", Appl. Opt. 13, 2693 (1974). CrossRef I. Yamaguchi, T. Zhang, "Phase-shifting digital holography", Opt. Lett. 22, 1268 (1997). CrossRef F. Zhang, I. Yamaguchi, L.P. Yaroslavsky, "Algorithm for reconstruction of digital holograms with adjustable magnification", Opt. Lett. 29, 1668 (2004). CrossRef I. Yamaguchi, "Holography, speckle, and computers", Optics and Lasers in Engineering 39, 411 (2003). CrossRef I. Yamaguchi, M. Yokota, "Speckle noise suppression in measurement by phase-shifting digital holography", Opt. Eng. 48 085602 (2009). CrossRef I. Yamaguchi, J. Kato, S. Ohta, "Surface Shape Measurement by Phase-Shifting Digital Holography", Opt. Rev. 8, 85 (2001). CrossRef I. Yamaguchi, J. Kato, H. Matsuzaki, "Measurement of surface shape and deformation by phase-shifting image digital holography", Opt. Eng. 42, 1267 (2003). CrossRef F. Zhang, J.D.R. Valera, I. Yamaguchi, M. Yokota, G. Mills, "Vibration Analysis by Phase Shifting Digital Holography", Opt. Rev. 11, 5 (2004). CrossRef